Temporomandibular disorders in elderly patients (Medical Journal of Indonesia, 2007)
Temporomandibular Disorders (TMD) is a disorder that is still controversial in terms of correlation between clinical signs & symptoms and age. Most studies were carried out on adult populations with little attention given to the elderly. The purpose of this study is to elucidate the frequency of TMD in elderly population and risk factors pertinent to it. This is a cross sectional study which included patients aged 60-91 of Geriatric Department of National Hospital Cipto Mangunkusumo, Jakarta, Indonesia. The temporomandibular joint (TMJ) was examined for clinical signs & symptoms. Data was analyzed using non parametric Chi Square test. Although there is no significant p value obtained, there is a clear tendency that occurence of TMD diminishes with age, more male elderly experience TMD and elderly experiencing up to 13 tooth loss might have higher risk for TMD. (Med J Indones 2007; 16:237-9)